Correction: Endoplasmic reticulum targeted chemotherapeutics: the remarkable photo-cytotoxicity of an oxovanadium(iv) vitamin-B6 complex in visible light. Issue 85 (10th October 2019) - Banerjee, Samya; Dixit, Akanksha; Shridharan, Radhika N.; Karande, Anjali A.; Chakravarty, Akhil R.
Abstract : Correction for ' Endoplasmic reticulum targeted chemotherapeutics: the remarkable photo-cytotoxicity of an oxovanadium(iv ) vitamin-B6 complex in visible light' by Samya Banerjee et al., Chem. Commun ., 2014, 50, 5590–5592.